2017
DOI: 10.7554/elife.24746
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-4 KIF21B is a potent microtubule pausing factor

Abstract: Microtubules are dynamic polymers that in cells can grow, shrink or pause, but the factors that promote pausing are poorly understood. Here, we show that the mammalian kinesin-4 KIF21B is a processive motor that can accumulate at microtubule plus ends and induce pausing. A few KIF21B molecules are sufficient to induce strong growth inhibition of a microtubule plus end in vitro. This property depends on non-motor microtubule-binding domains located in the stalk region and the C-terminal WD40 domain. The WD40-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
98
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(126 citation statements)
references
References 65 publications
(111 reference statements)
13
98
2
Order By: Relevance
“…Proteomic studies identified 3 kinesins expressed during male gametogenesis (kinesin-8B, -13 and -15)(Khan et al, 2005;Talman et al, 2014), but no functional studies have been conducted until now. In other eukaryotes, orthologues for kinesin-4, -5, -8B, -13 and -15 are known to be involved in microtubule dynamics and particularly mitosis and cilia/flagella length regulation(Almeida & Maiato, 2018;Hu et al, 2015;Ma, Wang, & Yang, 2017;Muhia et al, 2016;Niwa, 2015;Niwa et al, 2012;Shrestha, Hazelbaker, Yount, & Walczak, 2018;Singh, Pandey, Al-Bassam, & Gheber, 2018;van Riel et al, 2017). Unfortunately, concerning PBANKA_0622400, PBANKA_0609500, PBANKA_0809500, PBANKA_0902400 and PBANKA_1224100, no functional data are available and the number of species possessing orthologues of these proteins is currently very limited, making it difficult to construct any hypothesis concerning their roles.…”
mentioning
confidence: 99%
“…Proteomic studies identified 3 kinesins expressed during male gametogenesis (kinesin-8B, -13 and -15)(Khan et al, 2005;Talman et al, 2014), but no functional studies have been conducted until now. In other eukaryotes, orthologues for kinesin-4, -5, -8B, -13 and -15 are known to be involved in microtubule dynamics and particularly mitosis and cilia/flagella length regulation(Almeida & Maiato, 2018;Hu et al, 2015;Ma, Wang, & Yang, 2017;Muhia et al, 2016;Niwa, 2015;Niwa et al, 2012;Shrestha, Hazelbaker, Yount, & Walczak, 2018;Singh, Pandey, Al-Bassam, & Gheber, 2018;van Riel et al, 2017). Unfortunately, concerning PBANKA_0622400, PBANKA_0609500, PBANKA_0809500, PBANKA_0902400 and PBANKA_1224100, no functional data are available and the number of species possessing orthologues of these proteins is currently very limited, making it difficult to construct any hypothesis concerning their roles.…”
mentioning
confidence: 99%
“…Mutations in this regulatory coiled-coil relieve autoinhibition and lead to the disease congenital fibrosis of the extraocular muscles type 1 (CFEOM1) [4850]. An analogous regulatory coiled-coil segment plays a role in autoinhibition of KIF21B [51]. As noted by Bianchi et al [49], the regulatory coiled-coil segment of KIF21A shares 37.5% sequence similarity to amino acids 998-1077 of KIF7, suggesting that the mechanism of autoinhibition for KIF7 may involve interactions between this coiled-coil region and the motor domain.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, KIF7 and KIF27 decrease the microtubule growth rate and growth length, thus destabilizing microtubules [33, 37]. The influence of KIF21B on microtubule dynamics is unclear as one study suggested that KIF21B increases microtubule growth rates and another suggested that it decreases growth rates [51, 54].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations